DEVELOPMENT OF POP-UP BOOK MEDIA FOR INTRODUCING THE CONCEPT OF ISLAMIC PHILANTHROPY TO CHILDREN AGED 5 TO 6 YEARS (THUFULA, 2024)
This research aims to develop an interactive pop-up storybook to introduce the concept of Islamic philanthropy to children aged 5 to 6 in Kudus District. The research sample consisted of 49 children from two Raudlatul Athfal (RA) schools, selected using a multi-stage random sampling technique. The research method employed the ADDIE development model. Phase I analysis involved a literature review, institutional assessment, and media needs analysis. Phase II focused on conceptual media design. Phase III involved media construction and validation by experts. Phase IV included media implementation, and Phase V was the evaluation stage. Data analysis techniques encompassed both qualitative and quantitative methods. Expert validation results regarding children’s ability to understand Islamic philanthropy concepts indicated that all components were valid for measuring children’s comprehension according to early childhood development stages (ages 5 to 6). Paired sample t-test calculations yielded a t-value of 3.501, with a Sig (2-tailed) value of 0.001, indicating significance (p < 0.05). Data analysis concluded that the interactive pop-up storybook effectively introduces Islamic philanthropy concepts to children.